Importance of tumour volume and histology in trimodality treatment of patients with Stage IIIA non-small cell lung cancer—results from a retrospective analysis. (4th November 2021) - Joosten, Pieter J M; Dickhoff, Chris; van der Noort, Vincent; Smeekens, Maarten; Numan, Rachel C; Klomp, Houke M; van Diessen, Judi N A; Belderbos, Jose S A; Smit, Egbert F; Monkhorst, Kim; Oosterhuis, Jan W A; van den Heuvel, Michel M; et al.
Abstract: OBJECTIVES: Chemoradiotherapy (CRT) has been the backbone of guideline-recommended treatment for Stage IIIA non-small cell lung cancer (NSCLC). However, in selected operable patients with a resectable tumour, good results have been achieved with trimodality treatment (TT). The objective of this bi-institutional analysis of outcomes in patients treated for Stage IIIA NSCLC was to identify particular factors supporting the role of surgery after CRT. METHODS: In a 2-centre retrospective cohort study, patients with Stage III NSCLC (seventh edition TNM) were identified and those patients with Stage IIIA who were treated with CRT or TT between January 2007 and December 2013 were selected. Patient characteristics as well as tumour parameters were evaluated in relation to outcome and whether or not these variables were predictive for the influence of treatment (TT or CRT) on outcome [overall survival (OS) or progression-free survival (PFS)]. Estimation of treatment effect on PFS and OS was performed using propensity-weighted cox regression analysis based on inverse probability weighting. RESULTS: From a database of 725 Stage III NSCLC patients, 257 Stage IIIA NSCLC patients, treated with curative intent, were analysed; 186 (72%) with cIIIA-N2 and 71 (28%) with cT3N1/cT4N0 disease. One hundred and ninety-six (76.3%) patients were treated by CRT alone (high-dose radiation with daily low-dose cisplatin) and 61 (23.7%) by TT. The unweighted data showed that TT resulted in better PFS and OS. After weighting for factors predictive of treatment assignment, patients with a large gross tumour volume (>120 cc) had better PFS when treated with TT, and patients with an adenocarcinoma treated with TT had better OS, regardless of tumour volume. CONCLUSIONS: Patients with Stage IIIA NSCLC and large tumour volume, as well as patients with adenocarcinoma, who were selected for TT, had favourable outcome compared to patients receiving CRT. This information can be used to assist multidisciplinary team decision-making and for stratifying patients in studies comparing TT and definitive CRT. Abstract : Approximately 30% of patients diagnosed with non-small cell lung cancer (NSCLC) present with Stage III disease [1].